Pengembangan Modul Elektronik Berbasis STEAM (Science, Technology, Engineering, Art, and Mathematics)pada Materi Asam Basa - Sinaga, Kevin S.; Amdayani, Susilawati (Entalpi Pendidikan Kimia, 2025)
This study aims to develop an electronic module based on the STEAM (Science, Technology, Engineering, Art, and Mathematics) approach for acid-base material to enhance the quality of 21st-century chemistry learning. The background of this research lies in the lack of interactive and relevant learning media, especially in delivering acid-base concepts that are abstract and complex. This research employs a Research and Development (R&D) method using the 4D development model (Define, Design, Develop, Disseminate). The research subjects were twelfth-grade students at SMA Negeri 1 Percut Sei Tuan. Data were collected through interviews, observations, questionnaires, and tests. The instruments used include expert validation sheets to assess feasibility, teacher questionnaires to assess practicality, student questionnaires to assess responses, and achievement tests to measure effectiveness. The results showed that the developed electronic module met the criteria of being valid, practical, and effective. The module was created using Flip PDF Professional software and is equipped with interactive features such as videos, animations, and evaluation tools. Therefore, this module is deemed suitable to be used as an alternative learning medium for acid-base material.